Delay-tolerant hierarchical distributed control for DC microgrid clusters considering microgrid autonomy - Chen, Yongpan; Zhao, Jinghan; Wan, Keting; Yu, Miao (Applied energy, 2025)
A microgrid cluster (MGC) is formed by interconnected geographically adjacent microgrids (MGs), which can effectively improve power supply reliability. To fulfill the requirements of coordination between MGs while exerting the autonomy ability of each MG, this paper proposes a hierarchical distributed control method for DC MGCs with MG autonomous-cooperative mode switching. The proposed method can not only realize the proportional current sharing between the MGs and the voltage regulation of the common bus but also allow MGs to operate in autonomous or cooperative mode by establishing and disconnecting the inter-MG communication links. In addition, considering that the delay of inter-MG communication links affects multiple control links of the proposed control method, a delay-dependent stability analysis method based on Padé approximation and eigenvalue spectrum comparison is proposed. By stability analysis, the time delay margin (TDM) is determined, and the key link that determines the TDM is identified as the observer based on the proportional-integral (PI) consensus algorithm. On this basis, the scattering transformation (ST) is introduced to improve the stability of the observer under delay and thus enhance the TDM of DC MGCs, which is confirmed by stability analysis based on a new system model integrating node variables and edge variables. Finally, the performance of the proposed control method and stability analysis results are verified by hardware-in-loop (HIL) tests and MATLAB/Simulink simulations •A novel hierarchical distributed control method for DC MGCs is proposed.•The proposed control allows MGs to join in cooperation or operate autonomously.•How to identify the key control link determining the time delay margin is studied.•The scattering transformation approach is introduced to improve system stability.•A new system model integrating node and edge variables is established for stability analysis.